Simbologia do uso de plantas medicinais por agricultores familiares descendentes de pomeranos no Sul do Brasil - Delpino, Gabriela Barcelos (2011)
In all ages and cultures man has learned to take advantage of local natural resources, including the use of medicinal plants. Understanding that each culture is composed of a web of meanings that will guide the actions of men in their daily lives, they will assign different meanings to these symbols present in their culture. Therefore, the symbology of the use of medicinal plants is particular in each culture and can have different meanings. This work aimed to investigate the meanings of the use of medicinal plants to the family farmers descendants of Pomeranians living in São Lourenço do Sul / RS and know the symbology of the use of medicinal plants in health care from the perspective of these farmers. The research was qualitative, descriptive and exploratory, held in São Lourenço do Sul. This study is part of the research "Bioactive plants for human use by families of farmers from ecological base in southern Rio Grande do Sul", developed by the School Nursing, Federal University of Pelotas and Temperate Climate Embrapa. The study included five farming families descendants of Pomeranians, selected from the snowball methodology, proposed by Goodman. The data collection occurred from January to June 2011. The instruments used were semi-structured interviews, participant observation, photographic record of plants and georeferencing. It was used the thematic analysis. Within the symbolic universe of the farmers are descendants of Pomeranians there are different meanings attributed to the use of medicinal plants. The main symbols were observed: medicinal plant as an economic symbol, as a symbol of the first care of health, as a religious symbol and medicinal plant associated with symbology of food. The medicinal plant is considered easy acquisition by being present in the environment and because it is a more economical alternative before of allopathic medicinesIt symbolizes a connection between the symbol of care and economic value. These seek to maintain a healthy diet and they try to include the use of medicinal plants in their day to day. With regard to religion in this community is strong and regulates the mode of thinking and acting of the descendants of Pomeranians. It is important that the nurse knows the values and beliefs and how these relate to medicinal plants. Should consider that the care is a construct made with the subjects and for that it is necessary to understand the symbols present, valuing human action, the day to day social group and the various interpretations that they make in everyday life, so that their health action be effective. The nurse must understand that under the gaze of other symbologies the medicinal plant is not seen as a medicine, but takes on different meanings.